2016
DOI: 10.17159/2413-3108/2015/v27i4a1264
|View full text |Cite
|
Sign up to set email alerts
|

Different tissue type categories of overuse injuries to cricket fast bowlers have different severity and incidence which varies with age

Abstract: Background. Cricket fast bowlers have a high incidence of injury and have been the subject of previous research investigating the effects of previous injury, workload and technique. Bone stress injuries are of particular concern as they lead to prolonged absences from the game, with younger bowlers appearing to be at particular risk. Objectives. To investigate the variation in severity and incidence of injury to different tissue types in fast bowlers and ascertain whether age is a significant risk factor for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Young fast bowlers were most susceptible to suffering LSF, consistent with previous research in fast bowlers17 26 27 as well as across other activities which involve repetitive loading of the lumbar spine including gymnastics, rowing and javelin 25. This is possibly due to the failure to achieve the necessary bone resilience28 to withstand repetition of substantial loading of fast bowling, which generates large ground reaction forces2 combined with extreme multiplanar trunk movements,1 which places large torsional, shear and compressive stress on the lumbar spine 29–31.…”
Section: Discussionsupporting
confidence: 82%
“…Young fast bowlers were most susceptible to suffering LSF, consistent with previous research in fast bowlers17 26 27 as well as across other activities which involve repetitive loading of the lumbar spine including gymnastics, rowing and javelin 25. This is possibly due to the failure to achieve the necessary bone resilience28 to withstand repetition of substantial loading of fast bowling, which generates large ground reaction forces2 combined with extreme multiplanar trunk movements,1 which places large torsional, shear and compressive stress on the lumbar spine 29–31.…”
Section: Discussionsupporting
confidence: 82%
“…This may be due to the differences in age group in each study, as it has been demonstrated the type of tissue injured varies between different age groups of fast bowlers and that different workload patterns resulted in different Injuries. 27,28 It has been found that younger bowlers were more likely to sustain bone stress injuries whereas older bowlers were more likely to sustain tendon injuries 27 and other studies have found that high medium term workload increased risk of bone stress injuries but reduced the risk of tendon injuries. 28 The individual variations in risk could be due to other moderating factors not examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A greater amount of acute load accumulated in high-speed running combined with a low high-speed running chronic load was also associated with a greater injury risk (relative risk=2.6) 57. Blanch et al 85 demonstrated that young cricket fast bowlers (<22 years) were 3.7–6.7 times more likely to suffer a bone injury than other players, while older fast bowlers (>31 years) were 2.2–2.7 times more likely to sustain a tendon injury than younger bowlers.…”
Section: What’s Next For Practitioners and Researchers?mentioning
confidence: 99%
“…For example, both younger and older athletes,85 86 and those with poorly developed physical qualities (eg, aerobic fitness, speed, repeated-sprint ability and lower body strength),47 54 84 low heart rate variability87 and low chronic training load54 86 have increased risk with a given spike in workload (figure 5). Large changes in throwing load (>60% per week) were associated with a twofold increase in shoulder injury rate (HR=1.9) and the effects of moderate (20%–60% per week) and large (>60% per week) increases in training load were exacerbated in the presence of poor external rotational strength and scapular dyskinesis 51.…”
Section: Myth 4: 15 Is the Magic Acwrmentioning
confidence: 99%